PAKISTAN-INDIA RELATIONS: PEACE THROUGH BILATERAL TRADE - Muhammad Ali; Noreen Mujahid; Aziz ur Rehman (European Scientific Journal, ESJ, 2015)
The idea behind this study is to identify the importance of trade in Pak-India peace process. This study emphases that trade is instrumental in achieving and maintaining peace and stability in the Indian subcontinent. Economic interdependence promotes peace and mutual economic benefits preclude war between nations and this concept has been argued in the paper. Furthermore, considering Pakistan-India trade relations; barriers to bilateral trade; current trade volume; measures needed to be adopted for improving bilateral trade and its role in Indo-Pak peace negotiations, territorial and border disputes and peace settlement have been analyzed. It is, therefore, concluded that trade can play a soft and positive role in conflict resolution between the two long standing adversaries.